Assessing the Knowledge of HIV among Engineering College Students and their Attitude toward People Living with HIV - Raja, V. Pragadeesh; Lenin, Dharani (Medical Research and Its Applications Vol. 3, 2024)
Aim: This study was conducted to assess the knowledge of HIV among engineering college students and their attitude toward people living with HIV. Introduction: The human immunodeficiency virus (HIV) is a serious worldwide public health issue that arises from a retrovirus that infects immune system cells in humans, either killing or severely weakening them. The patient exhibits no symptoms in the early stages of the infection. HIV can spread through unprotected sexual contact, contaminated needle exchanges, contaminated blood transfusions, and mother-child transmission. In 2022, globally, 39 million people are living with HIV and 630000 people died from HIV-related causes. The total number of people living with HIV in India is estimated at 24.01 lakh people in 2021. Materials and Methods: A cross-sectional study was done among college students from engineering colleges in Pondicherry from April 2018 to September 2018. The selection of study subjects was done using simple random sampling. After getting informed consent from the individuals a pre-tested, semi-structured questionnaire was administered. Data were entered and analysed using Microsoft Excel spreadsheets. Descriptive statistics were used and results were expressed as proportions. Results: The majority of the students, about 92.4% had heard about HIV/AIDS, and about 92.4% of the participants were aware that HIV can spread through body fluids such as blood, sexual contact, and urine. More than half 52.7% of students are aware that migrant workers, lorry drivers, and commercial sex workers are high-risk groups for HIV/AIDS. 68.8% of students don’t know their HIV status. 65.2% were not willing to isolate HIV-infected people from society. Regarding the attitude toward people living with HIV, the results of this study, are still discriminatory. The majority of the students were willing to accept and support the HIV patient, but this was not adequate and still, some stigma persists. Conclusion: More health education and campaigns to raise student knowledge of HIV/AIDS are urgently needed. The Ministry of Education discovered more effective ways to disseminate the required knowledge on HIV/AIDS via the Internet, social media, mobile apps, hotlines, booklets, and printed instructional materials.